HBsAg-Negative, Anti-HBc–Negative Patients Still Have a Risk of Hepatitis B Virus–Related Hepatitis after Autologous Stem Cell Transplantation for Multiple Myeloma or Malignant Lymphoma - Park, Hyunsung; Kim, Do Young; Kim, Soo-Jeong; Chung, Haerim; Cho, Hyunsoo; Jang, Ji Eun; Cheong, June-Won; Min, Yoo Hong; Song, Jae-Woo; Kim, Jin Seok (Cancer research and treatment, 2018)
Although hepatitis B surface antigen (HBsAg)-negative, hepatitis B core antibody (anti-HBc)-negative patients are not considered to be at risk for hepatitis B virus (HBV)-related hepatitis, the actual risk remains to be elucidated. This study aimed to evaluate the risk of HBV-related hepatitis in HBsAg-negative, anti-HBc-negative patients receiving autologous stem cell transplantation (ASCT) for multiple myeloma (MM) or malignant lymphoma. We retrospectively reviewed data from 271 HBsAg-negative patients (161 anti-HBc-negative and 110 anti-HBc-positive at the time of ASCT) who received ASCT for MM or lymphoma. The risk of HBV-related hepatitis was analyzed according to the presence of anti-HBc. HBV serology results at the time of ASCT were compared with those at the time of diagnosis of MM or lymphoma. Three patients (two anti-HBc-negative MMs and one anti-HBc-positive MM) developed HBV-related hepatitis after ASCT. The rate of HBV-related hepatitis did not differ among patients with or without anti-HBc status (p=0.843). HBV-related hepatitis more frequently occurred in MM patients than in lymphoma patients (p=0.041). Overall, 9.1% of patients (16.7% with MM and 5.4% with lymphoma) who were HBsAg-negative and anti-HBc-positive at the time of diagnosis had lost anti-HBc positivity during chemotherapy prior to ASCT. Our data suggest that HBsAg-negative, anti-HBc-negative patients at the time of ASCT for MM or lymphoma still might be at a risk for HBV-related hepatitis.